Pengembangan Materi Qirā’ah Berbasis Cerita Rakyat Palembang dengan Pendekatan TPACK - Salwa Humairoh; Kristina Imron; Imansyah Imansyah (ALSYS, 2026)
Arabic language learning, particularly qirā’ah skills, still faces challenges related to the limited availability of teaching materials that are contextual, engaging, and relevant to students’ lives. Generic qirā’ah materials with limited local cultural content tend to reduce learning interest and make it difficult for students to understand reading texts. This study aimed to develop qirā’ah materials based on Palembang folktales using the Technological Pedagogical Content Knowledge (TPACK) approach and to test their feasibility and effectiveness in Arabic language learning. This study used a Research and Development (R&D) method by adapting the Borg and Gall model, which was simplified into seven stages, namely needs analysis, planning, product development, expert validation, revision, limited trial, and product refinement. The research subjects were seventh-grade students of MTsN 1 Palembang. Data were collected through observation, interviews, documentation, questionnaires, and qirā’ah comprehension tests. The results showed that the developed qirā’ah materials were considered highly feasible based on assessments by material, language, and media experts. Students’ responses to the teaching materials were also in the very good category in terms of comprehensibility, attractiveness, and practicality. In addition, the use of qirā’ah materials based on Palembang folktales with the TPACK approach was proven effective in improving students’ literal and inferential reading comprehension. The conclusion of this study confirms that the development of qirā’ah materials based on local wisdom and integrated with the TPACK approach can serve as an innovative alternative to improve the quality of Arabic language learning in madrasahs.